USE OF CONTROL STANDARDS IN THE STUDY OF FLEXIBILITY AND MOBILITY OF THE SHOULDER JOINT - Novakova, L. V.; Kos, M. V. (Achievements of Clinical and Experimental Medicine, 2023)
SUMMARY. The article deals with the results of the study of the flexibility and mobility of the shoulder joint of gym visitors. The aim – theoretical and experimental substantiation of the need to use control standards for studying the flexibility of the shoulder joint. Material and Methods. They used a gymnastic stick, a centimeter tape, a tape measure, and a goniometer. 24 people who passed tests on the flexibility and mobility of the shoulder joint were examined. Results. The mobility of the shoulder joint improved in all participants of the experiment (in the control and experimental groups), which indicates the positive effect of physical exertion on the development of physical qualities. Conclusions. Flexibility is closely related to another physical quality – strength. Strength exercises performed without flexibility exercises lead to limited joint mobility. In our experiment, there was a combination of these two physical qualities, which gave a positive result in improving the indicators of flexibility and mobility of the shoulder joint.